Modeling the predictive role of music teachers’ job commitment and optimism in their sense of self-efficacy - Du, Yadian (Frontiers in Psychology, 2023)
Introduction: Teachers’ psychological factors have been argued to influence various aspects of music education. However, scant research has explored the psycho-affective aspects of music teachers’ work. To solve this shortage of research, this study examined the predictive role of Chinese music teachers’ job commitment and academic optimism in their self-efficacy. Methods: To this end, 340 music teachers from four universities in Henan province completed an online survey including three questionnaires. Results: The results of structural equation modeling (SEM) and regression analysis demonstrated that music teachers’ self-efficacy could be positively and significantly predicted by their optimism and job commitment. Discussion: The study provided implications for music education to pay further attention to the psychology of teaching in this field. Finally, directions for further research are presented to scholars, who are interested in the psycho-emotional side of music education.